MiR-497-5p down-regulates CDCA4 to restrains lung squamous cell carcinoma progression - Jiangwei Hu; Xinqin Xiang; Wei Guan; Weihua Lou; Junming He; Jian Chen; Yin Fu; Guoliang Lou (Journal of Cardiothoracic Surgery, 2021)
Abstract Background So far, few have concerned miR-497-5p in lung squamous cell carcinoma (LUSC). Methods MiR-497-5p expression in LUSC was measured by qRT-PCR. Its impacts on tumor-related cell behaviors were investigated by CCK8 assay, scratch healing assay, flow cytometry and Transwell invasion methods. In addition, interaction between miR-497-5p and CDCA4 in LUSC was also elucidated through rescue experiment, western blot, dual-luciferase, and bioinformatics analysis. Results Low level of miR-497-5p was confirmed in LUSC tissue and cells. Overexpressed miR-497-5p markedly inhibited cancer progression. miR-497-5p restrained CDCA4 expression. Rescue assay showed that overexpressing miR-497-5p eliminated effect of overexpressed CDCA4. Conclusion By targeting CDCA4, miR-497-5p restrained development of LUSC.